“Do not drink with her or with him?” Towards the interpretation of Sirach 9:9 - Sizikov, Aleksandr (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. I, Bogoslovie, filosofii͡a, 2023)
In this paper, the author deals with the problem of Biblical literary criticism on the example of one of the problematic readings of Ben Sira (9:9). The majority of translations of Ben Sira are made either from the Greek sources or from Greek and Hebrew sources, achieving a certain textual compromise. The Greek text is usually corrected on the basis of the Hebrew text, however there are cases where the Hebrew text is corrected on the basis of the Greek one, and the emendations are introduced. Such an approach ignores the fact that Biblical books existed and were transmitted in various recensions, which were altered independently. Therefore, there reconstruction of the common archetype is hardly possible. The example of Ben Sira 9:9 contains a regulation for a young man to drink wine during a banquet, however, this regulation varies in different sources. There are not so many written evidences about banquets in Judea in the time prior to the events described in the Maccabean books, so the Ben Sira is one of the principal sources of information. The Greek text prohibits to drink wine and to talk to a married woman during a banquet, the restriction presupposes a married woman was admitted to such events and to be able to choose freely who to converse with. The Latin sources prohibit to recline with a married woman and to drink wine with her. The Hebrew text advises to avoid drinking wine with a husband and conversing with him. Most of the translations ignore the witness of the Hebrew text, a popular vocalized reconstruction of the original contains an emendation on the basis of the Greek text: the masculine pronoun is replaced with feminine one. The detailed analysis of the pericope Ben Sira 9:1–9 suggests the Hebrew text is apparently primary one, and the Latin and the Greek translations reflect social realties of Roman and Greek banquets respectfully.